2003
DOI: 10.2139/ssrn.459740
|View full text |Cite
|
Sign up to set email alerts
|

Regime Shifting: The TRIPs Agreement and New Dynamics of International Intellectual Property Lawmaking

Abstract: restating and reviewing claim by developed countries that intellectual property rights "attract foreign investment, increase taxes, create new jobs, and facilitate technology transfer," and citing numerous supporting authorities) (footnotes omitted).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
175
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 173 publications
(177 citation statements)
references
References 16 publications
1
175
0
1
Order By: Relevance
“…In the area of plant genetic resources, however, Raustiala and Victor (2004) found that distinct, nonnested regimes had begun to overlap: regimes operating in issue areas previously seen as distinct, such as biodiversity and trade, had both come to affect plant genetic resources. In this situation rule inconsistencies can easily arise-indeed, actors intentionally create inconsistencies through 'regime shifting' (Helfer, 2004)-and are diffi cult to resolve. Inconsistencies also create opportunities for forum shopping by targets, which may undercut regulation.…”
Section: Transnational Climate Change Governance As a Regime Complexmentioning
confidence: 99%
See 1 more Smart Citation
“…In the area of plant genetic resources, however, Raustiala and Victor (2004) found that distinct, nonnested regimes had begun to overlap: regimes operating in issue areas previously seen as distinct, such as biodiversity and trade, had both come to affect plant genetic resources. In this situation rule inconsistencies can easily arise-indeed, actors intentionally create inconsistencies through 'regime shifting' (Helfer, 2004)-and are diffi cult to resolve. Inconsistencies also create opportunities for forum shopping by targets, which may undercut regulation.…”
Section: Transnational Climate Change Governance As a Regime Complexmentioning
confidence: 99%
“…Those arguments are bounded in two signifi cant ways. First, they focus predominantly on interstate regimes (Aggarwal, 1998;Alter and Meunier, 2009;Helfer, 2004;Oberthür and Gehring, 2011;Raustiala and Victor, 2004), albeit with a few signifi cant exceptions (Green, 2011;Kelley, 2009). Second, they are primarily concerned with regimes that promulgate legally binding rules; in the 'soft law' world of RSS a number of implications do not hold.…”
mentioning
confidence: 99%
“…Die Einschätzung, dass bei den Bern-Plus-Elementen einseitig auf die Interessen der Rechteinhaber Rücksicht genommen wurde, wird auch in der Literatur relativ einhellig geteilt (vgl. Matthew 2002;Kretschmer 2003;Helfer 2004;Heineke 2006). Ein profaner Grund hierfür ist das historische Zuspätkommen von Akteuren aus dem Bereich der "Zivilgesellschaft", halten doch beispielsweise Braithwaite und Drahos (2000: 72, unsere Hervorh.…”
Section: Regulierungswettbewerb In Den Bereichen Politik Und Marktunclassified
“…This same phenomenon is often referred to as "forum shopping" (Busch 2007;Sykes 2008), "regime shifting" (Helfer 2004), or "institutional choice" (Jupille and Snidal 2006;Jupille, Mattli, and Snidal 2013). As scholars emphasize the diversity of institutionalized cooperation in world politics, the choice of partners for collaboration has become increasingly important.…”
Section: Introductionmentioning
confidence: 99%